2008
DOI: 10.4049/jimmunol.181.11.7985
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of CXCR3 Signaling due to CXCL10 Deficiency Impairs the Antiviral Response to Herpes Simplex Virus 1 Infection

Abstract: The chemokine, CXCL10, chemotactic for NK cells, activated T cells, and dendritic cells is highly expressed during viral infections, including HSV-1. The importance of this chemokine to the control of HSV-1 infection was tested using mice deficient in CXCL10 (CXCL10−/−). Following corneal infection, HSV-1 viral titers were elevated in the nervous system of CXCL10−/− mice, which correlated with defects in leukocyte recruitment including dendritic cells, NK cells, and HSV-1-specific CD8+ T cells to the brain ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
86
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(90 citation statements)
references
References 66 publications
(95 reference statements)
4
86
0
Order By: Relevance
“…The authors suggested that recruitment of CXCL10-expressing hematopoietic cells, dendritic cells, NK cells, and HSV-specific CD8 ϩ T cells to the brain stem plays a role in controlling viral replication in the nervous system (60). CXCL10 deficiency was associated with a reduction in the mobilization of HSV-specific CD8 ϩ T cells into the brain as a result of dysregulation of CXCR3 signaling (31). CXCR3 Ϫ/Ϫ deficient mice are also reported to be susceptible to primary genital HSV-2 infection (61)(62)(63)(64).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors suggested that recruitment of CXCL10-expressing hematopoietic cells, dendritic cells, NK cells, and HSV-specific CD8 ϩ T cells to the brain stem plays a role in controlling viral replication in the nervous system (60). CXCL10 deficiency was associated with a reduction in the mobilization of HSV-specific CD8 ϩ T cells into the brain as a result of dysregulation of CXCR3 signaling (31). CXCR3 Ϫ/Ϫ deficient mice are also reported to be susceptible to primary genital HSV-2 infection (61)(62)(63)(64).…”
Section: Discussionmentioning
confidence: 99%
“…Wuest and Carr have previously demonstrated that, following corneal HSV-1 infection, both CXCL10 and CXCR3 played a role in reducing primary infection in the nervous system (31). The authors suggested that recruitment of CXCL10-expressing hematopoietic cells, dendritic cells, NK cells, and HSV-specific CD8 ϩ T cells to the brain stem plays a role in controlling viral replication in the nervous system (60).…”
Section: Discussionmentioning
confidence: 99%
“…CXCL10 is an inflammatory chemokine that mainly recruits activated T cells and NK cells to sites of infection and/or inflammation. Using mouse animal models, it has been shown that CXCL10 expression is significantly induced and plays a critical role in a variety of viral infections, including infection with measles virus (20), West Nile virus (21), lymphocytic choriomeningitis virus (42), murine hepatitis virus (19,22), and herpes simples virus (24,43). The primary function of CXCL10 in these viral diseases is to recruit effector cells to the sites of infection.…”
Section: Discussionmentioning
confidence: 99%
“…CXCL10 has been reported to play an important role in host defense following a variety of viral infections. Using CXCL10 2/2 mice, the major function for CXCL10 in host defense against viral infection has been shown to be recruitment of effector T cells and NK cells to sites of infection/inflammation (19)(20)(21)(22)(23)(24)(25). However, CXCL10 function specific to DENV infection has not been examined in vivo.…”
Section: Engue Virus (Denv)mentioning
confidence: 99%
“…Indeed, dysregulation of CXCR3 signaling impairs antiviral responses in vivo. 31 Moreover, CXCR3 is essential, in association with CXCR4, for CD56 bright NK-cell recruitment to the endometrium during the menstrual cycle and in the decidua during pregnancy. 32 Furthermore, CD56 bright NK cells recruited through CXCR3 engagement in psoriatic skin are key players in the pathogenesis of psoriasis.…”
Section: Discussionmentioning
confidence: 99%